2006
DOI: 10.1021/jp063366s
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Soft X-ray Photoelectron Spectroscopic Studies and Scanning Auger Microscopy Studies of the Air Oxidation of Alkylated Silicon(111) Surfaces

Abstract: High-resolution soft X-ray photoelectron spectroscopy was used to investigate the oxidation of alkylated silicon(111) surfaces under ambient conditions. Silicon(111) surfaces were functionalized through a two-step route involving radical chlorination of the H-terminated surface followed by alkylation with alkylmagnesium halide reagents. After 24 h in air, surface species representing Si + , Si 2+ , Si 3+ , and Si 4+ were detected on the Cl-terminated surface, with the highest oxidation state (Si 4+ ) oxide sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
113
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(119 citation statements)
references
References 43 publications
(124 reference statements)
5
113
1
Order By: Relevance
“…As the authors concluded, 150 their observations strongly support an oxidative protective mechanism largely due to Si-C bonds disrupting the native oxide growth mechanism 80 and not exclusively resulting from limited access of oxygenated species to the substrate. 32,115,152 Despite the vast literature now available on the tandem chlorination/alkyl Grignard route, 74,102,109,114,124,145,148,150 and the general agreement over the high quality of the reaction product, the most obvious limitation of this methodology appears to be the complicated and inefficient (see Section 3.1) derivatization of films having a C n H 2n+1 structure. Further, the need for stringent conditions (such as the exclusion of water and oxygen) for both the chlorination (generally phosphorus(V) chloride with radical initiators) and the Grignard reaction might discourage the routine use of this two-step strategy.…”
Section: Alkylation Of Halide-terminated Surfacesmentioning
confidence: 79%
See 4 more Smart Citations
“…As the authors concluded, 150 their observations strongly support an oxidative protective mechanism largely due to Si-C bonds disrupting the native oxide growth mechanism 80 and not exclusively resulting from limited access of oxygenated species to the substrate. 32,115,152 Despite the vast literature now available on the tandem chlorination/alkyl Grignard route, 74,102,109,114,124,145,148,150 and the general agreement over the high quality of the reaction product, the most obvious limitation of this methodology appears to be the complicated and inefficient (see Section 3.1) derivatization of films having a C n H 2n+1 structure. Further, the need for stringent conditions (such as the exclusion of water and oxygen) for both the chlorination (generally phosphorus(V) chloride with radical initiators) and the Grignard reaction might discourage the routine use of this two-step strategy.…”
Section: Alkylation Of Halide-terminated Surfacesmentioning
confidence: 79%
“…31 As such, regardless of the chemical strategy used, complete passivation of the Si (111) surface cannot be achieved due to van der Waals interactions between methylene units of adjacent alkyl chains. 31,150 Second, alkylated and methylated Si(111) surfaces prepared via this route have a satisfactory stability in air 150 and show remarkable electrical properties, 114,145 with the lowest surface recombination velocity (o25 cm s À1 ) reported to date for a passivated (non-hydride-terminated 72 ) silicon surface. 151 The low recombination velocity of charge carriers is supporting evidence that there is a negligible number of surface defect sites (trap density o3 Â 10 À9 cm À2 ).…”
Section: Alkylation Of Halide-terminated Surfacesmentioning
confidence: 97%
See 3 more Smart Citations